Oxalis pes-caprae L. (Oxalidaceae): From Invasive Concern to Promising Bioresource for Health and Sustainable Applications - Giuseppe Antonio Malfa; Simone Bianchi; Vivienne Spadaro; Claudia Di Giacomo; Francesco Maria Raimondo; Rosaria Acquaviva (Plants)
Oxalis pes-caprae L., an invasive plant from South Africa, has developed into a severe ecological threat in many Mediterranean and temperate areas by replacing native flora and modifying ecosystems. Although this species has detrimental effects on the ecosystem, it has unrealized potential as a significant bioresource. Current research on the secondary metabolites found in O. pes-caprae, such as phenolic acids, oxalates, and flavonoids, is summarized in this review, along with an analysis of their biological and pharmacological properties, which include antibacterial, antidiabetic, and antioxidant activities. O. pes-caprae could be converted from a troublesome intruder into a financially and ecologically advantageous bioresource of natural products for pharmaceutical, nutraceutical, cosmetic, and agricultural applications by rethinking the invasive species as a resource for phytochemical extraction. This would offer a novel approach to managing invasive species while promoting the advancement of green technologies and sustainable practices.